'A Fair Day's Wage for a Fair Day's Work'? Exploring the connection between the parliamentary work of MPs and their electoral support. Issue 1 (2nd January 2019) - Bouteca, Nicolas; Smulders, Jef; Maddens, Bart; Devos, Carl; Wauters, Bram
ABSTRACT: Electoral systems across Europe increasingly invite candidates to build up a personal reputation to earn votes. In this article, we investigate whether parliamentary work can be considered as a personal vote-earning attribute for incumbent MPs based on data of the 2014 elections in Belgium. The results show that when parliamentary work is operationalised in a narrow way (i.e. as the number of bills and the number of oral and written questions of an MP), this has no influence on the amount of preferential votes. When parliamentary work is defined in a broader way (i.e. also including other aspects of the legislative and control function of MPs), parliamentary work has a significant positive effect for MPs from opposition parties. This supports the claim that the number of legislative and control activities is not sufficient to measure the impact of parliamentary work on preferential votes, but that also other aspects of the work should be taken into account.